2015
DOI: 10.1111/cbdd.12493
|View full text |Cite
|
Sign up to set email alerts
|

3‐Keto‐1,5‐bisphosphonates Alleviate Serum‐Oxidative Stress in the High‐fat Diet Induced Obesity in Rats

Abstract: Obesity has become a leading global health problem owing to its strong association with a high incidence of oxidative stress. Many epidemiologic studies showed that an antioxidant supplementation decreases the state of oxidative stress. In the present work, a HFD-induced rat obesity and oxidative stress were used to investigate the link between fat deposition and serum-oxidative stress markers. We also studied the effect of a chronic administration of 3-keto-1,5-bisphosphonates 1 (a & b) (40 μg/kg/8 weeks/i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…HOMA‐IR, an essential indicator of systemic IR, is now elevated with HFD induction and relieved with LQ treatment. Previous studies have reported that the NAFLD model constructed by HFD is a high‐fat‐feeding obesity model, but the model is widely used in NAFLD research (Lahbib et al, 2015; Sui et al, 2023; Yan et al, 2022). With our current results, we found that LQ affected not only lipid metabolism but also glucose metabolism, so this suggests that the improvement of fatty liver by LQ may be accomplished through glucolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…HOMA‐IR, an essential indicator of systemic IR, is now elevated with HFD induction and relieved with LQ treatment. Previous studies have reported that the NAFLD model constructed by HFD is a high‐fat‐feeding obesity model, but the model is widely used in NAFLD research (Lahbib et al, 2015; Sui et al, 2023; Yan et al, 2022). With our current results, we found that LQ affected not only lipid metabolism but also glucose metabolism, so this suggests that the improvement of fatty liver by LQ may be accomplished through glucolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%